2020
DOI: 10.1002/smll.202005571
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Quasi‐Bilayer Subnano Metal‐Oxide Interfacial Cluster Catalysts for Advanced Catalysis

Abstract: Planar metal clusters possess high metal utilization, distinct electronic properties, and catalytic functions from their 3D counterparts. However, synthesis of these materials is challenging due to much elevated surface free energies. Here it is reported that silica supported planar bilayer Pt‐CoOx subnano clusters, consisting of approximately one atomic layer of Pt and one CoOx layer on top, can be achieved by employing strong‐electrostatic interactions during impregnation and precisely‐controlled CoOx coatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…[13] Next, NiO x ALD was performed on Pt 1 /C 3 N 4 for another cycle by alternatively exposing nickelocene (NiCp 2 ) and O 3 at 200 °C to achieve the dimeric Pt 1 Ni 1 /C 3 N 4 catalyst (Scheme 1). [14] In this case, Ni atoms nucleate on the predeposited Pt atoms as well as the open C 3 N 4 support by forming Pt 1 Ni 1 dimers along with isolated Ni 1 atoms. To obtain the Pt 1 + Ni 1 HDSAC (denoted as Pt 1 + Ni 1 /C 3 N 4 ), ALD was executed by sequentially exposing the C 3 N 4 support to MeCpPtMe 3 , NiCp 2 , and O 3 at 200 °C; therein, steric hindrance between chemisorbed MeCpPtMe 3 and NiCp 2 precursors ensures the inhibition of direct nucleation of NiCp 2 on Pt, and O 3 was used to simultaneously remove the ligands of chemisorbed MeCpPtMe 3 and NiCp 2 precursors to form the Pt 1 + Ni 1 HDSAC.…”
Section: Catalyst Synthesis and Structure Characterizationmentioning
confidence: 99%
“…[13] Next, NiO x ALD was performed on Pt 1 /C 3 N 4 for another cycle by alternatively exposing nickelocene (NiCp 2 ) and O 3 at 200 °C to achieve the dimeric Pt 1 Ni 1 /C 3 N 4 catalyst (Scheme 1). [14] In this case, Ni atoms nucleate on the predeposited Pt atoms as well as the open C 3 N 4 support by forming Pt 1 Ni 1 dimers along with isolated Ni 1 atoms. To obtain the Pt 1 + Ni 1 HDSAC (denoted as Pt 1 + Ni 1 /C 3 N 4 ), ALD was executed by sequentially exposing the C 3 N 4 support to MeCpPtMe 3 , NiCp 2 , and O 3 at 200 °C; therein, steric hindrance between chemisorbed MeCpPtMe 3 and NiCp 2 precursors ensures the inhibition of direct nucleation of NiCp 2 on Pt, and O 3 was used to simultaneously remove the ligands of chemisorbed MeCpPtMe 3 and NiCp 2 precursors to form the Pt 1 + Ni 1 HDSAC.…”
Section: Catalyst Synthesis and Structure Characterizationmentioning
confidence: 99%
“…Kinetic studies revealed that the mass-specific rate at room temperature was 5.21 mol CO h –1 g Pt –1 over 1cFe-Pt/SiO 2 , which is about 30 times greater than that for Pt/Fe 2 O 3 (Figure c). Similar results were also found on FeO x -coated Ir/SiO 2 and CoO x -coated Pt/SiO 2 samples in the PROX reaction. , In this work, in situ XAFS measurements showed that atomically dispersed Fe 1 (OH) x species on Pt NPs exhibited a strikingly high reducibility, a fact that can be reduced from Fe 3+ to Fe 2+ at room temperature by H 2 , which is sharply distinct from the reduction of Fe n (OH) x clusters above 200 °C. Such a strikingly high reducibility might play an important role in the high performance of 1cFe-Pt/SiO 2 .…”
Section: Oxide Decoration Of Metal Particlesmentioning
confidence: 99%